Egypt eternal [videorecording (DVD)] : the quest for lost tombs - Bucher, Amy; Morton, Joe, 1947- (National Geographic Television, 2009)
This National Geographic Special shows treasures from the Cliffside of Tombs to the Valley of the Golden Mummies.